Hubungan Karakteristik Dengan Kejadian Skoliosis Pada Siswa Sekolah Menengah Pertama Swasta Al Muslimin Pandan - Nurul Dinah Nabilah; Liza Agustin; Trisno Susilo; Lagut Sutandra (Jurnal Kesehatan dan Fisioterapi, 2022)
Background: Scoliosis is a spinal disorder that can interfere with a person's activities and body shape. The prevalence of scoliosis in Indonesia is not known for certain but according to some scoliosis research is more common in girls with low BMI and use heavy bag. General symptoms that are often seen in scoliosis sufferers are spinal abnormality (“C” or “S” form). Scoliosis can be detected by measuring the curvature of spine using a scoliometer. Objective: This study aimed to investigate the correlation of the characteristic to scoliosis of student at SMP Swasta Al Muslimin. Method: The study design is observational analytic with cross-sectional approach. The determination of sample used the purposive sampling wirh a sample of 83 respondent who fulfill the inclusion and exclusion criteria. The respondents were measured their body mass index which obtained from weight dan height of respondents and their scoliosis were measured with the scoliometer. The result of study were analyzed with Chi square. Result: There is association between sex to scoliosis and there are not association between BMI and bag weight to scoliosis. Conclusion:  Sex is related to scoliosis while BMI and bag weight is not related to scoliosis of students at SMP Swasta Al Muslimin.Keyword: Characteristic, Sex, BMI, Scoliosis.